Pengaruh Tingkat Pendidikan, Pengalaman Kerja, Pelatihan Terhadap Akuntabilitas Penyusunan Keuangan Dana Desa (Studi Kasus Kantor Desa Kramat, Desa Kambu, Desa Malaju, Desa Lasi Kec. Kilo Kab. Dompu) - Lesi Anjaliati; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The village is the spearhead of development for the welfare of the community. Therefore, village development is an important role that must be carried out because it contains elements of equality and can be directly enjoyed by the village community so that it can improve the welfare of the community. The research method used is a quantitative research method with primary data obtained from questionnaire data measured using a likert scale. The total population in this study is the entire apparatus of kramat village, Kambu village, Malaju village and Lasi kec. Kilo village, Dompu Regency. The sampling technique used in this study was to use a saturated sample with a total of 53 respondents. The data analysis technique used is a multiple linear regression test that is processed with the help of the SPSS 23.0 for windows program. The results of this study show that (1) The level of education has a positive effect on the accountability of village fund financial preparation. (2) Work experience has a positive effect on the accountability of Village Fund Financial Preparation. (3) The training has a positive effect on the accountability of the Village Fund Financial Preparation, and (4) that there is no effect of the Training on the accountability of the Village Fund Financial Preparation.Keyword: Accountability financial preparation, Level of education, Work experience, training